OCCUPATIONAL WELL-BEING OF SPECIALISTS WITH DIFFERENT LEVEL OF TRUST TO EQUIPMENT - Akimova, A. Yu. (Modern Psychology, 2019)
The results of the study of the occupational well-being of employees of locomotive railway brigades with different levels of trust to equipment are presented. The trust to equipment is considered a psychological attitude of the specialists to the technique, which arises and manifests as a result of interaction with it. The non-linear relationships of the level of trust of specialists to the equipment with indicators of occupational wellbeing have been established. If the trust to equipment is of medium or high level, satisfaction with professional achievements, professional self-acceptance and the overall indicator of occupational well-being has higher values than at low levels.